Pengaruh Profesionalisme, Komitmen Organisasi, Locus Of Control dan Etika Profesi Pada Kinerja Auditor - Hidayah Dwi Lestari; Ersi Sisdianto (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
Accountant has important role on supplying a reliablle finance information for all stakeolder. To support auditor success its very important for the auditor themself to has hight quality and reliable perfomance. To assess auditor performance in public accountant are based on the auditor performance. An auditor when implamanting their duty are requred to produce a good performance. A good audit quality can be generated if an auditor is able to pay attention to the factors that influence it. Professionalism, organizational commitment, locus of control (internal) and professional ethics are some factors that may affect audit performance. This study aims to obtain empirical evidence of professionalism, organizational commitment, locus of control (internal) and professional ethics on audit performance.The location of this research was conducted at seven Public Accounting Firm in Bali Province with total sample of 66 auditors. The sample was chosen using saturated sampling technique. Data collection in this research using survey method with questionnaire technique. Data analysis technique used is Multi linear regression technique. This study show a valid result on instrument test and clasic asumtion test. Based on the analysis conducted, professionalism, organizational commitment, locus of control (internal) and professional ethics have significant and positive effect on audit performance. This study conclude that if the auditors are be able to increase their profesionalism, organizational commitment, locus of control (internal) and professional ethics their audit performance will increase al well.